Ichthyological diversity of Inambari River, Madre de Dios, Peru - Palacios, Vanessa (2008)
The main purposes of this study were to know the diversity of fishes in the Inambari river basin, at Mazuco district, (Madre de Dios) and the state of conservation of the aquatic habitats. Samples were collected from 22 stations using seines of small mesh (5mm) and recording data from each habitat. Taxonomic composition of fishes, diversity and abundance, ecological characterization by altitudinal range, habitat and water type; and the conservation state of each water bodies have been studied. A total of 1411 individuals were collected and four orders, 13 families, 35 genera and 52 species were identified. The groups with more diversity were Characiformes (65%) and Siluriformes (25%). Three new records for Peru: Serrapinnus notomelas, Pseudopimelodus bufonius y Pseudocetopsis gobiodes and one endemic species: Chaetostoma marcapatae have been register. The altitudinal pattern influence in micro habitats presence and as consequence in abundance and species richness; so higher richness and abundance were found in the lower zone (52 species and 1309 individuals), in streams (44 species) and rivers (712 individuals). According type of water, the clearwaters showed higher values of richness (37 species) and the whitewater higher abundance (789 individuals). The higher diversity indexes (H’) were found in the rivers, white waters and altitudes lower. The higher values of Index of Biological Integrity (IBI) were obtained in the main channel of the Río Inambari, up river of Mazuko and lower values in the Mirador stream, down river of Mazuko, where it was observed gold mining activity artisanal.